Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given $a,b,c,d \in \mathbb{Z}$, there is $x,y$ such that

$$(a^2 + b^2)(c^2 + d^2) = x^2 + y^2$$

One can show this by considering the complex number $a + bi$ and $c+ di$, using complex properties to deduce that $x = ac - bd, y = ad + bc$ is a solution. However, given that either $a^2, b^2$ are distinct or $c^2,d^2$ are distinct, then how can one can find nonzero solutions $x,y$?

Sorry, I am assuming $a,b,c,d$ are nonzero.

share|improve this question

2 Answers 2

If $a=b=0$ or $c=d=0$, obviously we cannot do it.

If one of (say) $a$ or $b$ is $0$, and one of $c$ or $d$ is $0$, there will be situations in which we cannot do it, for instance when $a=c=3$, $b=d=0$.

If one of $a$ or $b$ is $0$, but the other is not, and neither $c$ nor $d=0$, there is no difficulty.

Now examine the case all of $a$, $b$, $c$, $d$ are non-zero. Without loss of generality we may assume they are all positive.

Use the formulas $$(a^2+b^2)(c^2+d^2)=(ac+bd)^2+(ad-bc)^2=(ad+bc)^2+(ac-bd)^2.$$ We need only check that at least one of $ad-bc$ and $ac-bd$ is non-zero.

Suppose to the contrary that $ad=bc$ and $ac=bd$. Then (i) $a^2cd=b^2cd$ and (ii) $c^2ab=d^2ab$. Since none of $a$, $b$, $c$, $d$ is $0$, by cancellation we get $a^2=b^2$ and $c^2=d^2$.

share|improve this answer

This is not true if 2 or more of the variables are zero: for instance $(3^2 + 0^2)(3^2 + 0^2)$ can only be expressed as $9^2 + 0^2$, and $(3^2+4^2)(0^2 + 0^2)$ is just trivial.

The case where exactly one of $a,b,c,d$ is $0$ is very simple. So I'll assume without loss of generality that all variables are non-zero, and in fact positive: $a,b,c,d > 0$. Let's also assume that of the two possibilities, $a^2,b^2$ are distinct. In this case it is obvious that $y > 0$, so the only question is whether $x = 0$.

This happens only if $ac = bd$, or $a/b = d/c$. If we happen to be so unlucky, just swap the values of $a$ and $b$ to get a new $x'$ and $y'$. This has no effect on the value of $a^2+b^2$ or on the positivity of $y'$, but now $x' = 0$ iff $b/a = d/c$, which can't happen as this would mean $a/b = b/a \implies a^2 = b^2$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.